2005
DOI: 10.1084/jem.20050768
|View full text |Cite
|
Sign up to set email alerts
|

Secretory leucoprotease inhibitor binds to NF-κB binding sites in monocytes and inhibits p65 binding

Abstract: Secretory leucoprotease inhibitor (SLPI) is a nonglycosylated protein produced by epithelial cells. In addition to its antiprotease activity, SLPI has been shown to exhibit antiinflammatory properties, including down-regulation of tumor necrosis factor α expression by lipopolysaccharide (LPS) in macrophages and inhibition of nuclear factor (NF)-κB activation in a rat model of acute lung injury. We have previously shown that SLPI can inhibit LPS-induced NF-κB activation in monocytic cells by inhibiting degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
233
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(248 citation statements)
references
References 32 publications
12
233
1
2
Order By: Relevance
“…In other studies, SLPI-deficient mice were reported to be more sensitive to LPS-induced shock; their macrophages had higher IL-6 and NF-kB activity, suggesting that SLPI attenuates excessive inflammatory responses. 49 Taggart, Greene, and co-workers 50,51 demonstrated that SLPI downregulates TNF-α expression induced by LPS by inhibiting degradation of IkBp and binds directly to NF-kB in a site-specific manner. More recently, E 2 was found to protect against Human Immunodeficiency Virus Tat protein-induced inflammatory reactions in vascular endothelium by blocking NF-kB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, SLPI-deficient mice were reported to be more sensitive to LPS-induced shock; their macrophages had higher IL-6 and NF-kB activity, suggesting that SLPI attenuates excessive inflammatory responses. 49 Taggart, Greene, and co-workers 50,51 demonstrated that SLPI downregulates TNF-α expression induced by LPS by inhibiting degradation of IkBp and binds directly to NF-kB in a site-specific manner. More recently, E 2 was found to protect against Human Immunodeficiency Virus Tat protein-induced inflammatory reactions in vascular endothelium by blocking NF-kB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, overexpression of SLPI suppresses NFKB activation (Jin et al 1997, Sano et al 2003, Henriksen et al 2004. It can prevent proteosome-dependent IkBb degradation (Lentsch et al 1999) and also directly bind to NFKB consensus sites on DNA, inhibiting transcription (Taggart et al 2005). Wound healing and tissue remodelling are other processes involving the anti-leukoproteinases.…”
Section: Natural Antimicrobial Peptides (Naps)mentioning
confidence: 99%
“…Along with its extracellular antiprotease activity, rSLPI also exhibits intracellular activity in alveolar macrophages as it is here that it exerts an anti-inflammatory activity by binding to nuclear factor (NF)-kappa B binding sites (Taggart et al, 2005). The encapsulation of rSLPI within liposomes that are specifically taken up AMs can therefore be regarded as a targeted carrier system.…”
Section: Discussionmentioning
confidence: 99%